lec01 part 2 - g ( x ) f ( x ) dx Must be able to integrate...

Info iconThis preview shows pages 1–8. Sign up to view the full content.

View Full Document Right Arrow Icon
1 - Integration by Parts Per-Olof Persson persson@berkeley.edu Department of Mathematics University of California, Berkeley Math 1B Calculus
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Integrals Indefinite Integrals Z f ( x ) dx = F ( x ) means F 0 ( x ) = f ( x ) Result is a function (or a family of functions) Definite Integrals, Fundamental Theorem of Calculus Z b a f ( x ) dx = ±Z f ( x ) dx ² b a Result is a number
Background image of page 2
The Substitution Rule The Substitution Rule Z f ( g ( x )) g 0 ( x ) dx = ± u = g ( x ) du = g 0 ( x ) dx ² = Z f ( u ) du Example Z 2 xe x 2 dx = ± u = x 2 du = 2 xdx ² = Z e u du = e u + C = e x 2 + C
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Integration by Parts Integration by Parts Z f ( x ) g 0 ( x ) dx = f ( x ) g ( x ) - Z g ( x ) f 0 ( x ) dx Proof. Recall product rule for differentiation : d dx [ f ( x ) g ( x )] = f ( x ) g 0 ( x ) + g ( x ) f 0 ( x ) Integrate: f ( x ) g ( x ) = Z ± f ( x ) g 0 ( x ) + g ( x ) f 0 ( x ) ² dx Rearrange: Z f ( x ) g 0 ( x ) dx = f ( x ) g ( x ) - Z g ( x ) f 0 ( x ) dx
Background image of page 4
Integration by Parts Integration by Parts Z f ( x ) g 0 ( x ) dx = f ( x ) g ( x ) - Z g ( x ) f 0 ( x ) dx Alternative Notation Let u = f ( x ) and v = g ( x ) . Then du = f 0 ( x ) dx and dv = g 0 ( x ) dx . The integration by parts formula becomes: Z udv = uv - Z v du
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Integration by Parts Example Z xe x dx = ± f ( x ) = x, f 0 ( x ) = 1 g 0 ( x ) = e x , g ( x ) = e x ² = xe x - Z e x dx = xe x - e x + C = e x ( x - 1) + C Example Z ln xdx = ± f ( x ) = ln x g 0 ( x ) = 1 ² = x ln x - Z x · 1 x dx = x ln x - Z 1 · dx = x ln x - x + C
Background image of page 6
How to Choose f ( x ) and g 0 ( x ) Integration by Parts Z f ( x ) g 0 ( x ) dx = f ( x ) g ( x ) - Z
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 8
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: g ( x ) f ( x ) dx Must be able to integrate g ( x ) Must be able to integrate g ( x ) f ( x ) LIATE rule Choose f ( x ) as high up as possible: Logarithmic (e.g. ln x ) Inverse Trigonometric (e.g. sin-1 x ) Algebraic (e.g. x-3 ) Trigonometric (e.g. sin x ) Exponential (e.g. e x ) Denite Integrals Denite Integrals Z b a f ( x ) g ( x ) dx = [ f ( x ) g ( x )] b a-Z b a g ( x ) f ( x ) dx Example Z 9 4 ln y y dy = " f ( y ) = ln y, f ( y ) = 1 y g ( y ) = 1 y , g ( y ) = 2 y # = [ln y 2 y ] 9 4-Z 9 4 2 y 1 y dy = 6 ln 9-4 ln 4-Z 9 4 2 y dy = 6 ln 9-4 ln 4-[4 y ] 9 4 = 6 ln 9-4 ln 4-4...
View Full Document

Page1 / 8

lec01 part 2 - g ( x ) f ( x ) dx Must be able to integrate...

This preview shows document pages 1 - 8. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online